Sustainable food yard activities at RA Miftahussalam Adiwiyata School to support english, science, and math literacy of young learners - Thoyyibah, Luthfiyatun; Fatimah, Ai Tusi; Ratnawati; Tusriyah (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2024)
Early childhood education is an important period in a child's development. During this time, children are curious and enjoy learning through play. This is the perfect opportunity to impart various knowledge and skills, including English, science and mathematics. The Sustainable Food Yard (P2L) in Adiwiyata schools can be an effective medium to improve the English, science and maths literacy of early childhood students. P2L provides a contextual and fun learning space for students to learn about various things such as plants and the environment. This community service activity was aimed to 1) Provide field learning experiences through plant media; 2) Improve English literacy skills through contextualised plant media integrated with learning; 3) Raise awareness among RA Miftahussalam students about eating vegetables that can be grown on limited land; 4) Raise awareness about the importance of protecting the environment; 5) Support Adiwiyata schools in achieving their goal which was encouraging the creation of knowledge and awareness among school members in environmental protection efforts through the environmental care and culture movement at school. This activity was carried out using the mentoring method. The team assisted RA Miftahussalam students and teachers in learning how to plant on limited land, learn English, science and basic mathematics with plant media and use the results. The result of this community service gave students and teachers experience of good practices from P2L activities by planting and eating vegetables grown around them. The results of this assistance become a reference for innovative learning at the RA Miftahussalam to be further developed to support environmentally friendly behavior at Adiwiyata schools.